﻿Cost-effectiveness of treatment intervention in prediabetic patients in Bulgaria - Stanislava Yordanova; Konstantin Mitov; Maria Kamusheva (Pensoft Publishers, 2023)
Introduction: The study aims to evaluate the cost-effectiveness (CE) of an early intervention in prediabetes (metformin) in order to prevent or slow down the onset of diabetes in those at high risk compared with the current "do nothing" approach. Materials and methods: An Excel-based model was developed. The results of the CE and cost-utility analyses are presented as an ICER (incremental cost-effectiveness ratio) and ICUR (incremental cost-utility ratio), respectively. Markov model of the cost or potential savings from the perspective of the National Health Insurance Fund in Bulgaria was performed. Results: The ICER of the metformin intervention in prediabetes patients compared with "do nothing" routine shows that metformin treatment produced more health benefits (number of prevented diabetes cases) on a lower cost for the public payer. The ICER calculated is -7,122.32 BGN per number of prevented diabetes cases and it confirms cost-savings are possible when metformin is applied compared with the "do nothing" approach. The ICUR per quality-adjusted life years (QALYs) gained also shows the metformin preventive intervention as a dominant and cost-saving alternative. The Markov model simulation confirms the intervention with metformin is less costly in a long-term and leads to higher QALYs. Conclusion: The investment in a preventive intervention with metformin offers an excellent value for money. The ICER of the metformin intervention in prediabetes patients compared with "do nothing" routine shows that metformin preventive intervention produced more health benefits on a lower cost for the public payer in Bulgaria.